Handbuch Audiovisuelle Translation Arbeitsmittel für Wissenschaft, Studium, Praxis - Künzli, Alexander; Kaindl, Klaus (Audiovisual Translation Studies, 2024)
This handbook provides compact, well-founded and comprehensible information on the entire spectrum of audiovisual translation, or AVT for short. In five thematic sections, 30 experts provide a comprehensive overview of theoretical and methodological approaches as well as the various forms of audiovisual translation: from subtitling and dubbing to video game translation, audio description and surtitling in theater and opera. In addition to the current state of research on AVT and the latest - technological - developments, desiderata from research and voices from the field will also be considered. Get to know central issues of AVT research and learn more about institutional aspects, especially about the German-speaking AVT landscape. Extensive bibliographies point the way for teachers and students to in-depth reading and scholarly study and provide a good starting point for professional action in the field of audiovisual translation.